Analisis Jeda Waktu Pembacaan Imaging Plate Terhadap Signal to Noise Ratio pada Citra Computed Radiography - Dwi Rochmayanti; Defia Ayusari; Andrey Nino Kurniawan (Poltekkes Kemenkes Semarang, 2015)
Backgroud: Imaging plate (IP) is a storage media on computed radiography (CR). IP that has been exposed and does not process immediately will decrease the latent image exponentially over time and degrade the image quality. Normally, 25% of signal will be lost if IP was scanned at 10 minutes till 8 hours after exposure. So It will decrease the image quality. Image quality is determined by several factors. One of them is the signal-to-noise ratio (SNR). This study aims to determine the effect of reading time delay of IP to SNR on CR image.Methods: This research was a quantitative study with an experimental approach. Population of this study was CR digital image with various time delay of IP reading. Samples were 51 digital images of water phantom read by IP reading with time interval was 0 hours, 0.5 hours, 1 hour; 1.5 hour, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours and 8 hours after exposure. Image pixel value and noise was weasured by ImageJ software to determine the value of SNR, then analyzed statistically with the regression test.Results: There was effect of reading time delay to SNR on CR image. Time delay affected 30,5% decreasing of SNR. Generally, time delay of IP reading decrease the SNR. The average decrease was 1.55% of SNR.Conclusion: The decrease of the SNR value was not big enough, only 1.55%. However, it will better when IP read as soon as possible after exposure to reduce the decrease of image quality.